2017
DOI: 10.4314/ejesm.v10i4.3
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of vehicle inspection operations to traffic system in Abuja, Nigeria

Abstract: The general view about the routine vehicle inspection operations is to ensure that vehicles

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…There are researches on the safety of roads that have been carried out in the world in general and in Nigeria in particular (Whitelegg,1983;Sunmaila,1992;CARRS -Q,2007;Mahmud & Hoque, 2011;Sunmola, 2012;Alade,2012;Filibus, 2012;Badejo,2014;Faniran & Bello, 2014;Sunmola, 2014;Raji et al,2014;Edorhe, 2014;Stephens et al, 2015;Adenigbo et al,2016); Gbadamosi & Adenigbo, 2017;Ojekunle et al, 2017)and Yusuf et al (2018) as well as Babalola (in press). Whitelegg (1983) argued that Road Traffic accidents will continue to be a severe challenge globally if the misconception of blame apportioning, responsibilities, or engineering inadequacies continued to be used to explain RTAs.…”
Section: Review Of Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…There are researches on the safety of roads that have been carried out in the world in general and in Nigeria in particular (Whitelegg,1983;Sunmaila,1992;CARRS -Q,2007;Mahmud & Hoque, 2011;Sunmola, 2012;Alade,2012;Filibus, 2012;Badejo,2014;Faniran & Bello, 2014;Sunmola, 2014;Raji et al,2014;Edorhe, 2014;Stephens et al, 2015;Adenigbo et al,2016); Gbadamosi & Adenigbo, 2017;Ojekunle et al, 2017)and Yusuf et al (2018) as well as Babalola (in press). Whitelegg (1983) argued that Road Traffic accidents will continue to be a severe challenge globally if the misconception of blame apportioning, responsibilities, or engineering inadequacies continued to be used to explain RTAs.…”
Section: Review Of Literaturementioning
confidence: 99%
“…On the other hand, Gbadamosi and Adenigbo (2017) examined the contribution of Vehicle Inspection operations to the traffic system in Abuja, Nigeria, and suggested that the Inspection Officers must inspect the components of vehicles properly before the vehicle registrations are done. Ojekunle et al (2017) analysed road users' perception of road safety in Minna, Niger State, Nigeria, and Yusuf et al (2018) analysed the trends, challenges, and forecast of road traffic accidents in Nigeria while Babalola (in press) discussed the trends and distributions of road traffic crashes and injuries in Nigeria between 2013 and 2016.…”
Section: Review Of Literaturementioning
confidence: 99%
See 1 more Smart Citation